Subtype identification of clinical and thrombus imaging features in acute ischemic stroke: using clustering analysis and principal component analysis - Wenjuan Wu; Yue Cheng; Long Chen; Qingyue Fu; Jingxuan Jiang; Lei Zhang; Ximing Wang (Scientific Reports)
Abstract Acute ischemic stroke (AIS) presents significant heterogeneity in clinical and thrombus imaging characteristics, which can profoundly impact therapeutic decisions and outcomes. This study analyzed 520 AIS patients who underwent endovascular thrombectomy, integrating clinical variables and thrombus imaging features to identify potential subtypes through unsupervised clustering and principal component analysis. Three distinct subtypes emerged: Cluster 1, characterized by middle cerebral artery occlusion, shorter thrombus lengths, and favorable outcomes; Cluster 2, comprising predominantly male smokers and drinkers with no significant outcome differences; and Cluster 3, consisting of older patients with higher stroke severity, internal carotid artery occlusion, longer thrombus lengths, and poor outcomes. Key features driving subtype differentiation included atrial fibrillation, thrombus perviousness, and clot burden scores. Significant variations in recanalization and hemorrhagic transformation rates were also observed among clusters. These findings underscore the potential of integrating thrombus imaging characteristics into personalized treatment strategies, offering a more precise approach to prognosis and management for AIS patients.